Alcohol use amongst older adults: Knowledge and beliefs of occupational therapists working in physical health care settings. (May 2015) - Maclean, Fiona; Gill, Jan; O'May, Fiona; Breckenridge, Jenna
Introduction: There is little discussion in the United Kingdom occupational therapy literature surrounding the topic of older people and alcohol, despite the growing prevalence of alcohol-related health problems in older adults resulting from an ageing population and changing patterns of consumption. Occupational therapists in physical health care settings are likely to work with older people whose drinking pattern may not be alcohol dependent, but may put their physical or psychological health at risk. Method: A survey methodology was employed using open and closed questions, recruiting occupational therapists (band 5 to 9) ( n = 122) working with older people (65+ years) in physical health care settings across all, except one, National Health Service Regional Health Boards in Scotland. Results: Responses highlight gaps in occupational therapists' knowledge around alternative 'safe limits' of alcohol intake for older people. Belief in professional role was evident, but the perception was that this was not supported by undergraduate education. Occupation focused theory and assessment were not prioritized when considering alcohol in the older adult. Conclusion: This study has highlighted a need to develop pre- and post-qualification education for occupational therapists, to enhance understanding of theory, assessment and knowledge of alcohol with older adults in physical health care settings.